2020
DOI: 10.1038/s41598-020-78973-0
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative material analysis using secondary electron energy spectromicroscopy

Abstract: This paper demonstrates how secondary electron energy spectroscopy (SEES) performed inside a scanning electron microscope (SEM) can be used to map sample atomic number and acquire bulk valence band density of states (DOS) information at low primary beam voltages. The technique uses an electron energy analyser attachment to detect small changes in the shape of the scattered secondary electron (SE) spectrum and extract out fine structure features from it. Close agreement between experimental and theoretical bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…5. It is known that the use of SEM secondary electron images (SEI) combined with energy dispersion analysis (EDA) is primarily an imaging method and not a fully quantitative approach [17]. It is difficult to identify CaCO unambiguously using this approach.…”
Section: Ivc Scanning Electron Microscopy Analysismentioning
confidence: 99%
“…5. It is known that the use of SEM secondary electron images (SEI) combined with energy dispersion analysis (EDA) is primarily an imaging method and not a fully quantitative approach [17]. It is difficult to identify CaCO unambiguously using this approach.…”
Section: Ivc Scanning Electron Microscopy Analysismentioning
confidence: 99%
“…The signal signature for this form of contamination is greatly reduced as the FIB window is created, and as post FIB SES indicate at the time points, it is observed that this contamination does start to return to the surface of the materials as the sample undergoes conventional SEM imaging. This finding revealed that as well as the ability of SES to monitor ACC, Plasma FIB Xe exposure has the capability to remove carbon contamination from the surface of Ti without the requirement for chemical surface treatments [ 23 ]. The removal of carbon contamination is seen as an advantage for IBID fabrication, notably for nanoconductors to improve the conductivity of the deposited material and to increase the tensile elasticity of FIB fabrication microstructures [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability to monitor different forms of carbon contamination during the deposition process is still yet to be established. The most obvious reason for this is a lack of suitable characterisation tools is the combination of multiple requirements: high surface sensitivity (akin to X-ray photoelectron spectroscopy (XPS), high spatial resolution (akin to Auger electron spectroscopy) [ 21 ], and the ability to identify the carbon bonding present using low beam energies (reducing sample modification) without the need for an Ultra High Vacuum (UHV) [ 22 , 23 ]. All of these requirements may be fulfilled by Secondary Electron (SE) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These contrast modulations originate from the photoexcitation of local excess charge carrier distributions, which affect the configuration of surface states and the yield of SE emission. A less considered effect is that this change in charge distribution modifies the electric field outside the surface too, which in turn dynamically changes the SE collection in the SEM [1,2,4,5,6]. Both mechanisms, the changes in emission yield and in collection efficiency, contribute to the 2D dynamical SE patterns.…”
Section: Introductionmentioning
confidence: 99%